2004
DOI: 10.1099/vir.0.80333-0
|View full text |Cite
|
Sign up to set email alerts
|

Successful induction of ovine pulmonary adenocarcinoma in lambs of different ages and detection of viraemia during the preclinical period

Abstract: Ovine pulmonary adenocarcinoma (OPA) can be reproduced consistently in neonatal lambs by intratracheal injection of inocula containing jaagsiekte sheep retrovirus (JSRV). In this study, clinical disease, confirmed pathologically as OPA, was induced in a high proportion of lambs that had been inoculated intratracheally with infectious lung fluid at 1, 3 and 6 months of age. The incubation periods, however, were longer in these three age groups than in 1-week-old lambs that were used as controls. Viraemia was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 25 publications
3
46
0
Order By: Relevance
“…In addition, the results of this study showed that the rate of viral infection detected by real-time PCR is much higher compared to histopathological examination. This is in agreement with previous reports demonstrating that the number of JSRV infected animals is much higher than the number that will ever develop the disease (3,10,26). In addition, histopathological lesions were found in 11 out of 15 PCR positive samples, indicating higher sensitivity of real-time PCR.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, the results of this study showed that the rate of viral infection detected by real-time PCR is much higher compared to histopathological examination. This is in agreement with previous reports demonstrating that the number of JSRV infected animals is much higher than the number that will ever develop the disease (3,10,26). In addition, histopathological lesions were found in 11 out of 15 PCR positive samples, indicating higher sensitivity of real-time PCR.…”
Section: Discussionsupporting
confidence: 81%
“…As the tumour cells are secretory, a considerable amount of fluid can be generated and accumulated in the respiratory tract of the affected animals and the most typical feature of clinical OPA is the discharge of a whitish foamy fluid from the nostrils (De las Heras et al, 2003). The presence of the JSRV can be confirmed in the lung fluid or tumours by immunoblotting (Sharp and Herring, 1983), immunohistochemistry Palmarini et al, 1995;Salvatori et al, 2004), ELISA (Palmarini et al, 1995) and PCR (Bai et al, 1996;Palmarini et al, 1996b). In OPA affected sheep, JSRV is also detectable in cells of the lymphoreticular system, employing a highly sensitive PCR assay (Palmarini et al, 1996b;Holland et al, 1999) or immunohistochemistry (Holland et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…type II pneumocytes (also called alveolar type II cells) in the alveoli, and Clara cells in the bronchioli. Tumours exclusively occur in the sheep lung, as a result of selective replication of JSRV in these two cell types demonstrated by the detection of the viral protein only in the tumoural cells and their neighbouring epithelial cells [55,68,75]. However JSRV may infect different cell types in vitro, with a larger cellular tropism.…”
Section: Jsrv Tropismmentioning
confidence: 99%
“…Hence, ovine cell lines issued from various tissues may be infected in vitro by JSRV, however viral production stays weak [58]. Presence of viral DNA can be demonstrated in naturally infected animals in lymphoid tissues, alveolar macrophages and in peripheral blood mononuclear cells such as monocytes or B and T lymphocytes [29,33,37,56,75].…”
Section: Jsrv Tropismmentioning
confidence: 99%